The Degree of Teachers' Using the Modern Teaching Techniques in the Second Cycle Basic from their Point of View A Field Study in Lattakia City - عجيب, يحيى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to know the degree of using the modern Teaching techniques in the schools of the second cycle of basic education in the city of Lattakia from their point of view, and the difficulties of the degree of using, as well as to know the differences in the degree of using and the difficulties of applying according to the following variables (scientific and educational qualifications, Experience, training courses), use the descriptive approach. The sample included (194) teachers, for the academic year 2020-2021. To achieve the goal of the research, a questionnaire was designed consisting of (30) paragraphs, divided into two axes (first: the degree of teachers' using the modern teaching techniques, second the difficulties of teachers applying modern Teaching techniques). The results of the research showed that the research sample's estimate of the degree of teachers' using the modern Teaching techniques in the schools of the second cycle of basic education in the city of Lattakia came to a medium degree. The difficulties in implementing it were also high and it found that there are statistically significant differences in the using the modern Teaching techniques according to the variable of scientific and educational qualification in favor of teachers who hold the educational qualification diploma, and according to the variable of training courses, in favor of the teachers who followed training courses, and there are no statistically significant differences according to the variable experience, also cleared the presence of statistically significant differences in the evolution of teachers to due the difficulties in using the modern Teaching techniques according to the variable of scientific and educational qualifications in favor of teachers who hold the educational qualification diploma, and the absence of statistically significant differences in the degree of difficulties of their using the modern Teaching technologies Depending on the variables experience and training courses.